Gesamtkatalog der Gemälde / : Neue Galerie am Landesmuseum Joanneum - Skreiner, Wilfried; Steinle, Christa; Foitl, Alexandra; Wied, Alexander; Biedermann, Gottfried; Fenz, Werner; Schafschetzy, Margit; Schilcher, Beate; Silberbauer, Wolfgang (Graz : Neue Galerie am Landesmuseum Joanneum, 1988)
Abel, Josef ; Ableo ; Achten, Josef ; Adrian, Marc ; Aduatz, Friedrich ; de Alexandris, Sandro ; L'Allemand, Fritz ; L'Allemand, Sigmund ; Allgayer, Lorenz ; Allmer, Josef ; Alt, Franz ; Alt, Rudolf von ; Amerling, Friedrich von ; Amesbauer, Anton ; Ameseder, Eduard ; etc.
boek